Studies on the steam and CO2 reforming of methane for GTL-FPSO applications - Lee, Yun Ju; Hong, Suk-In; Moon, Dong Ju (ELSEVIER, 2011)
Steam CO2 reforming (SCR) of methane for the production of syngas was simulated using PRO-II and investigated over Ni-based catalysts for GTL-FPSO applications. The Ni-based catalysts were prepared by an impregnation method. The catalysts before and after the reaction were characterized by N-2 physisorption, XRD and TEM techniques. The conversion of CH4 was increased by increasing the concentration of H2O and CO2 in the feed. For the application in Co-based Fischer-Tropsch synthesis, the synthesis gas ratio of H-2/CO = 1.85-2.0 in the SCR was designed by the modeling of PRO-II simulator, and identified in a fixed bed reactor system by controlling the feed molar ratios of CH4:H2O:CO2. It was found that Ni/MgO catalyst is more desirable catalyst for the production of synthesis gas than Ni/gamma-Al2O3 and Ru/TiO2 catalysts on the point of the low carbon formation and suitable H-2/CO ratio for the GTL-FPSO applications with Co-based FT process. (C) 2011 Published by Elsevier B.V.
Keywords: FISCHER-TROPSCH SYNTHESIS; PARTIAL OXIDATION; GAS; CATALYST; SUPPORT; SYNGAS; NI